Wind shear enhances soil moisture influence on rapid thunderstorm growth - Christopher M. Taylor; Cornelia Klein; Emma J. Barton; Sebastian Hahn; Wolfgang Wagner (Nature, 2026)
Abstract Convective storms can develop rapidly, creating hazards to local populations through intense precipitation, strong winds and lightning 1 . The large-scale environment in which thunderstorms develop is often well captured in forecast systems, yet predicting where individual storms will initiate remains a fundamental challenge. It is known that differential heating driven by soil moisture (SM) patterns creates atmospheric circulations that favour convective initiation over drier soils 2,3 , whereas wind shear between low and mid levels can enhance storm growth 4,5 . Here we show that the most extreme initiations are especially favoured over SM contrasts by means of an interaction with wind shear. Analysing 2.2 million afternoon events across sub-Saharan Africa, we find 68% more initiations classed as extreme given favourable (versus unfavourable) soil conditions, with greatest vertical storm growth occurring where SM-driven circulations oppose the direction of shear-induced cloud displacement. Developing clouds follow the mid-level wind direction and, where this opposes the low-level flow, rainfall is strongly correlated with locally drier soils. Although such shear conditions are particularly common over tropical north Africa, the effect favours negative SM–precipitation feedbacks globally. The combination of SM heterogeneity and wind shear provides a potentially important source of predictability for where deep convection develops, particularly for the most rapidly developing thunderstorms.